2007
DOI: 10.2136/sssaj2005.0391
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Prediction of Soil Water Retention using Mid Infrared Spectroscopy

Abstract: Soil‐water properties vary widely with soil composition and texture, but measurements are often time consuming and expensive to determine using traditional laboratory methods. Mid‐infrared (MIR) spectroscopy is sensitive to soil composition, allowing multivariate calibrations to be derived between volumetric soil water retention and MIR spectra. Mid‐infrared partial least squares (PLS) models can be derived from the spectra of soils and reference data, and can be used to predict the water retention solely from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 25 publications
5
77
0
Order By: Relevance
“…On the basis of a chemisorption study, it was concluded that the band at 1640-1610 cm -1 was due to physically adsorbed water while the one at 1380 cm -1 was due to coordinatively bound water (Aochi, et al, 2011). Weak bands at about 1980, 1870 and 1790 cm -1 are attributed to quartz overtone (Janik, et al, 2007b;Nguyen, et al, 1991). In addition, clay mineral spectra show an intense complex band at around 1048 cm -1 , related to the stretching vibrations of Si-O groups, while the bands at 525 and 468 (Bishop, et al, 2008;Spence and Kelleher, 2012).…”
Section: Soil Mineral Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of a chemisorption study, it was concluded that the band at 1640-1610 cm -1 was due to physically adsorbed water while the one at 1380 cm -1 was due to coordinatively bound water (Aochi, et al, 2011). Weak bands at about 1980, 1870 and 1790 cm -1 are attributed to quartz overtone (Janik, et al, 2007b;Nguyen, et al, 1991). In addition, clay mineral spectra show an intense complex band at around 1048 cm -1 , related to the stretching vibrations of Si-O groups, while the bands at 525 and 468 (Bishop, et al, 2008;Spence and Kelleher, 2012).…”
Section: Soil Mineral Identificationmentioning
confidence: 99%
“…In particular the FTIR spectra of clay minerals made it possible to distinguish clay minerals from each other through the bands assigned to OH and Si-O groups (Bishop, et al, 2008;Madejova, 2003). Clays or aluminosilicates show two sharp peaks at 3695 and 3622 cm -1 due to OH stretching (Janik, et al, 2007b;Madejova, 2003;Nguyen, et al, 1991). A broad band near 3400 cm -1 is due to OH stretching (H bonded water); the position and intensity of this band is affected by various exchangeable cations.…”
Section: Soil Mineral Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectral peaks observed at 3,695, 3,657 and 3,626 cm -1 were attributed to the presence of -OH stretching band for kaolinite (Fig. 3a) (Schroeder 2002;Cornell and Schwertmann 2003;Janik et al 2007;Song et al 2012). The bands observed at 413, 428, 470 and 522 cm -1 in the spectra of soil samples (Fig.…”
Section: Mir Spectral Featuresmentioning
confidence: 99%
“…On the other hand, [16] demonstrated that soil physical properties based on soil solid composition and surfaces such as clay content and contraction-swelling potential can be reasonably predicted using MIR spectroscopy; [17] calibrated MIR reflectance spectra to estimate soil water content to several matrix pressure heads. Viscarra [2] performed a very complete review of the different soil attributes measured by NIR and MIR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%